Modelo de gestão dos resíduos sólidos urbanos como elemento de desenvolvimento regional sustentável: uma análise dos municípios do Oeste do Paraná - Bianco, Tatiani Sobrinho Del (2018)
The problem of urban solid waste management (RSU) is a topic of worldwide concern, and has been treated as a priority, since equating excessive generation and final disposal of environmentally sound waste is one of the major challenges facing modern society. Thus, the RSUs are correctly managed as a challenge / goal to be achieved, in order to minimize the negative impacts caused by the generation of waste from various generating sources. In view of the above, this thesis aimed to propose a model of MSW management differentiated, in the stages of collection, transportation, treatment and recovery of waste, capable of meeting the legal prerogatives in economic, social and environmental context, and that allows the implantation of an economic model that generates wealth, employment and income in a sustainable environment in the municipalities of the Western Mesoregion of Paraná. For that, the methodological procedures included the execution of six stages, namely: 1) Characterization of the sources of RSU in the western mesoregion of Paraná; 2) Estimation of the potential of RSU generation in the municipalities of the Western Mesoregion of Paraná, during the years 1980 to 2030; 3) Evaluation of the execution of the National Solid Waste Policy as of the enactment of Federal Law No. 12,3052010; 4) Prospecting of methods, processes and technologies for the collection, transport, treatment and use of MSW; 5) Presentation of the MSW management model that allows the consolidation of an economic and sustainable system based on the MSW industrialization based on the economic, social and environmental specificities of the municipalities of the West of Paraná; 6) Consolidation and systematization of results. The results showed that only 12% of the municipalities of the Western Mesoregion of Paraná presented, through the construction of the Indicator of Sustainable Regional Development, a dynamic relationship in their productive base with economic, social and environmental advances. However, given the potential increase in the generation capacity of the MSW in the region, which was estimated at around 41%, it was identified that the 50 municipalities had a daily solid waste generation potential of 595.6 ton/day, in 1980, to 841.5 ton/day, in 2030. Thus, it was evidenced that there is inability to comply with Federal Law No. 12.305/2010, where 63% of the municipalities of the West of Paraná do not have the capacity economic, financial and technical / intellectual staff capable of handling the costs of managing and maintaining the correct level of waste management. This result is mainly due to the application of PNRS guidelines and targets in the municipalities of the West of Paraná through individualized solutions (landfills and / or controlled landfills), which become sources of economic and financial problems for the municipal administrations, as well as in the unfeasible possibility of meeting all the determinations in effect in PNRS / 2010. This scenario also occurs when one intends to establish only one intermunicipal waste management consortium capable of serving the 50 municipalities in the region, since a total investment of R $ 936.28 million would be necessary considering the amount of waste generated in the region, by 2030. Thus, the feasible, economical, social and environmentally adequate solution to waste management in the municipalities of the West of Paraná is the use of three Integrated Systems of Solid Urban Waste Management (SIGRSU), which should be implanted in the Microregions of Cascavel, Foz do Iguaçu and Toledo. Thus, the implementation of this new MSW management model, based on differentiated methods and technologies, has demonstrated the technical and economic viability of the proposal, in which urban solid waste becomes a cost factor and becomes an investment opportunity. In this scenario, the economic variable is one of the main attractions for individuals, while the impacts on the environment and society are also positive. Therefore, there is an environmental externality transformed into a source of opportunities for new business models, in which waste is considered as raw material and / or input of industrial processes, which will help in the sustainable and innovative development of the Meso-region under study, since it would be capable of generating income, from the implementation and development of new technologies, increase the useful life and reduce the need to increase the area for landfills and, thus, make the municipalities comply with the guidelines of Federal Law N ° 12.305/2010, of the PNRS.